Bianchi type-III string cosmological models for stiff and anti-stiff fluid in general relativity - Amirhashchi, Hassan; Zainuddin, Hishamuddin (Hrvatsko Fizikalno Drustvo,Croatian Physical Society, 2010)
Bianchi type-III string cosmological models in the presence of stiff and anti-stiff fluids are studied. The scalar expansion is assumed to be proportional to the shear. In the present study, we consider two cases (i)p+ρ= 0 and (ii) p−ρ= 0, where ρ and p are the rest energy density and the pressure of the fluid, respectively. The physical behavior of these models is also discussed.